Arthroscopic Diagnosis and Treatment of Chronic Hip Pain After Total Hip Arthroplasty and the Role of Anterior Capsule Disruption in Iliopsoas Tendinopathy. Issue 6 (27th June 2019) - Nazal, Mark R.; Parsa, Ali; Martin, Scott D.
Background: The use of hip arthroscopic surgery in patients suffering from chronic hip pain after total hip arthroplasty (THA) has a limited presence in the literature, with most studies having limited follow-up. Purpose: The first goal of this study was to evaluate hip arthroscopic surgery in the diagnosis and management of patients with chronic hip pain after THA. The second goal was to describe a new cause of iliopsoas tendinopathy (IPT) involving disruption of the anterior capsule. Study Design: Case series; Level of evidence, 4. Methods: We conducted a retrospective analysis with prospectively collected clinical outcomes of patients after THA who underwent hip arthroscopic surgery for chronic hip pain without an identifiable cause. The patients were at least 18 years old and had a minimum follow-up of 24 months. Results: The retrospective analysis found that hip arthroscopic surgery led to new diagnostic information in 8 patients (80%). Of the 10 patients diagnosed with IPT, 4 (40%) lacked an anatomic cause; however, these patients had a history of difficult exposure of the anterior capsule and/or a lack of capsular repair during index THA. The mean modified Harris Hip Score (mHHS) was 71.9 ± 15.6, and the mean 6-month postoperative visual analog scale (VAS) pain score was 0.8 ± 2.2, which was significantly lower than preoperatively ( P = .0055). There was also significantly improved forward flexion range of motion ( P = .0183) and straight leg raise (SLR) strength test results ( P = .0263). Hip arthroscopic surgery resulted in 8 patients (80%) continuing to be pain-free at a mean follow-up of 6.8 ± 1.4 years, while 2 patients (20%) progressed to revision arthroplasty. There were no major or minor complications. Conclusion: Hip arthroscopic surgery was found to have an important role in the diagnostic and therapeutic management of patients with chronic hip pain after THA, with good clinical outcomes at a mean follow-up of 6.8 years and no complications. We believe that disruption of the anterosuperior acetabular capsule, including the reflected head of the rectus femoris, can allow the iliopsoas tendon to move intra-articularly and precipitate IPT. This disruption may be appreciated on the SLR strength test. Although this study presents a small sample size that cannot substantiate a cause-effect relationship, orthopaedic surgeons performing THA should consider minimizing disruption and/or ensuring repair of the anterior capsule to decrease this potential cause of IPT.